2021
DOI: 10.1177/21676968211016142
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Financial Identity Processes in Financial Behaviors and Financial Well-Being

Abstract: Financial identity formed during emerging adulthood is important for the regulation of youth financial behaviors, decisions, and long-term financial goals. This three-wave short-term longitudinal study investigates how youth develop a distinct manner of approaching and managing personal finances and reveals the structure and dynamics of financial identity development during emerging adulthood. Using the cross-lagged panel model analysis, it also investigates longitudinal reciprocal associations between financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…The primary sources of obtaining information on finances among school learners of form 12 in Latgale are parents and friends 71%, the Internet 69%, and mass media 53%. The data on financial literacy in the context of the linkage between the causes of family and youth financial literacy received within the present research has confirmed the conclusions obtained by other scientists (Vosylis et al, 2021;Jančius et al, 2022). Researches highlight the school's impact on youth financial literacy level (Kuzma et al, 2022;Compen et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…The primary sources of obtaining information on finances among school learners of form 12 in Latgale are parents and friends 71%, the Internet 69%, and mass media 53%. The data on financial literacy in the context of the linkage between the causes of family and youth financial literacy received within the present research has confirmed the conclusions obtained by other scientists (Vosylis et al, 2021;Jančius et al, 2022). Researches highlight the school's impact on youth financial literacy level (Kuzma et al, 2022;Compen et al, 2022).…”
Section: Discussionsupporting
confidence: 89%